Curriculum Bloom with Vitality - Jin, Lei (Journal of Theory and Practice of Social Science, 2023)
The world is colorful, and the curriculum should also be colorful. Teachers should not only be the executors of the curriculum, but also the developers, participants, and practitioners of the curriculum. To this end, we constantly explore and enrich the curriculum, allowing it to bloom with vitality. At this moment, my heart is so excited! Understanding the meaning of a word can actually trigger children's thinking about learning knowledge, understanding fairness and justice, and have a silent effect on moistening things. This is an unexpected gain! In fact, as long as we observe and think carefully in teaching, we will find that paying attention everywhere cultivates people, and paying attention everywhere is a lesson.